A novel mutation in ABCD1 gene in a Filipino patient with adult‐onset X‐linked ALD. Issue 5 (8th July 2020) - Porto, Kristine Joyce; Matsukawa, Takashi; Ishiura, Hiroyuki; Mitsui, Jun; Matic, Alexandria; Yu, Justine Megan; Dominguez, Jacqueline; Damian, Ludwig; Toda, Tatsushi; Tsuji, Shoji
Abstract: X‐linked adrenoleukodystrophy (X‐ALD) is the most common peroxisomal disorder caused by a mutation in ABCD1 gene. We present a 36‐year‐old, Filipino male, diagnosed with adrenomyeloneuropathy with later development of adult‐onset cerebral form of X‐ALD with a novel mutation c.2012T > C (p.Leu671Pro) in exon 10 of the ABCD1 gene. It is important that clinicians have high clinical suspicion because of the proven clinical efficacy of hematopoietic stem cell transplantation performed in the early stage of the disease.